HUBUNGAN SIBLING RIVALRY TERHADAP KESEHATAN MENTAL PADA ANAK USIA SEKOLAH DI KOTA PEKANBARU - Regar, Ersya Fanora Br; Bratha, Shinta Dewi Kasih (Ensiklopedia of Journal, 2025)
Abstract: Sibling rivalry is a rivalry that occurs between siblings caused by several factors in the family that can cause quarrels and greatly affect children's mental health. The purpose of this study is to find out the Sibling Rivalry Relationship to Mental Health in School-Age Children in Pekanbaru City. The research design used in this study is quantitative descriptive correlation, which is research that uses cross-sectional research methods. This research was conducted in Binawidya District, Pekanbaru on January 10 - 25, 2025, the sampling technique used the probability sampling technique, with a total of 99 children. Data collection tool is Questionnaire Mental Health and Sibling Rivalry analyzed by chi-square test. The results of this study were obtained by 60 respondents (60.6%) who experienced moderate sibling rivalry. Respondents had moderate mental health as many as 64 people (64.6%). There is a Sibling Rivalry Relationship on Mental Health in School-Age Children in Pekanbaru City with a p-value of 0.013. The conclusion of this study is that there is a Sibling Rivalry Relationship on Mental Health in School-Age Children in the City of Pekanbaru. The suggestion of this research is that parents are expected to pay more attention to the impact of sibling rivalry on children so that the development and growth of children can run well and to improve mental health in children. Keywords: Sibling Rivalry, Mental Health, School-Age Children